Medjezikovni stiki v besedju iz pomenskega polja kmetija v slovenskogoriškem narečju - Koletnik, Mihaela (University of Maribor Press, 2015)
Interlingual Contacts in the Word From the Semantic Field of the "kmetija" (Farm) in the Slovene Dialectic Dialect. Monograph Interlingual contacts in a word from the semantic field "kmetija" in the Slovenian dialect of the Slovene language by Mihaela Koletnik is an original scientific work that brings the results of research into the dialectal fund in the Pannonian area, where due to different historical circumstances many archaisms have been preserved. The author illuminates interlingual contacts, as reflected in the words of the Slovene-Gorski Kotar dialect of the Pannonian dialect group, which has been developing for centuries in the territory where Slavic, Germanic, Romance and Hungarian languages ​​come into contact. According to the SLA Questionnaire (232 questions), a dialect word describing a farmhouse, its premises and equipment, outbuildings and a farmyard was collected in twelve research points. The collected dialect word is commented on, analyzed by origin, presented geolinguistically on 216 lexical-word maps and compared with the same word in the adjacent Prekmurje and Prlek dialects, and its documentation and semantics in the older dictionaries and the Dictionary of Slovene Literary Language are analyzed. The author notes that the Pannonian vocabulary considered is quite diverse, and the diversity of the written names is further enhanced by their pronounced variety and here and there in the form of uniformity, but uniform enough for the possibility of outlining the individual arenas formed by the lexemes. The Slavic vocabulary, which represents the core of the Pannonian vocabulary, has been preserved especially in those areas where the Slavic vocabulary has already created a proper vocabulary, and the activity that it identifies has not changed much over the centuries (peasant work, peasant tools). In the external and internal arrangement of human habitation, however, the language was no longer so autonomous, which is quite understandable because of the advancement in the accommodation culture from pre-Slavic times; this set of words thus shows a greater proportion of the words taken over, which have spread to the dialect especially in recent centuries. The first Slovene monograph dealing with the subject of interlingual contacts, as reflected in the Slovene alphabet, is a valuable contribution to Slovene dialectology, which will enrich and supplement the knowledge of the Slovene language.